Analysis Of the Density and Diversity of Plant Species in Muhammadiyah University of Tasikmalaya (Field Research by PGSD Students of Muhammadiyah University of Tasikmalaya as an Implementation of Lecture Results of Science Basic Concept) - Mohammad Fahmi Nugraha; Nadiroh Nadiroh; Guspri Devi Artanti; Rahmayanti Ningsih; Mohammad Arfan Munajat; Meiliana Nurfitriani (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2023)
As living beings, apart from interacting with other humans, they also interact with living things and inanimate objects. These living things include animals, plants and inanimate objects such as air, water and soil. Therefore, humans are one of the living things that play a very important role in the survival of other creatures by establishing relationships with living things and inanimate objects around them. This study aims to measure the level of diversity and density of plant populations in the environment of Muhammadiyah University of Tasikmalaya. Primary data collection was carried out by using the quadratic method. The quadratic method is a method that uses sample plots, square, rectangular, and circle sample plots. The results of the research analysis show that in Muhammadiyah University of Tasikmalaya, in the biotic ecosystem, there are 36 species with a total of 70 individuals spread over 5 points. The results showed that the density and diversity of plants at Muhammadiyah University of Tasikmalaya were in the low category, and improvements had to be made immediately to create a green campus in the future.